Pengaruh Penggunaan Media Video Pembelajaran terhadap Pemahaman tentang Komunikasi dan Konseling Obat pada Mahasiswa S1 Farmasi: Influence of Use Video Learning Media on Understanding of Communications and Counseling Medicine in Undergraduate Students Pharmacy - Nurul Mardiati; Ratna Restapaty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Teaching-learning activities by lecturers are expected can use creative learning media with the use of appropriate media for the concepts to be conveyed to achieve the desired educational goals. Learning media is a tool used by lecturers to facilitate the delivery of learning materials. Learning media that can be used alone vary widely, one of which is learning video. This study aims to determine the influence of the use of video learning media on the understanding of communication and counseling drug on undergraduate students Pharmacy High School of Health Sciences Borneo Lestari Semester V Academic Year 2016/2017. This research is using the experimental method. The research design used was The Randomized Control-Group Pretest-Posttest Control Group Design. In this design, there are two groups that first randomly selected one class for the experimental group (using learning video) and one class for the control group (not using instructional video media). Sign value based on Wilcoxon test shows 0,025 <0,05. This indicates that there is the influence of t use of video learning media on the understanding of communication and counseling drug on undergraduate students Pharmacy High School of Health Sciences Borneo Lestari Semester V Academic Year 2016/2017.